Disposable plastic trays and their effect on polyether and vinyl polysiloxane impression accuracy: an in vitro study - Rues, Stefan; Stober, Thomas; Bargum, Thomas; Rammelsberg, Peter; Zenthöfer, Andreas (Clinical oral investigations, 2021)
To evaluate the dimensional accuracy of impressions taken by use of disposable stock plastic trays and to compare performance with that of metal trays.
Published online: 3 September 2020
Gesehen am 04.10.2021